Flat metal particles and manufacturing method thereof, and powdered iron core and manufacturing method thereof

By optimizing the manufacturing process of flat metal particles to control their peak intensity ratio, specific surface area, and recrystallization structure, the challenges of increased hysteresis losses in conventional particles are addressed, resulting in improved magnetic properties for iron cores.

JP7654247B2Active Publication Date: 2025-04-01NAT UNIV CORP KYUSHU INST OF TECH (JP)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021046881
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-22
Publication Date
2025-04-01
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

Conventional flat metal particles used in iron cores exhibit improved magnetic permeability and flux density but suffer from increased hysteresis losses, which lead to energy loss in motors.

Method used

The development of flat metal particles with a specific peak intensity ratio in X-ray diffraction, a controlled specific surface area, and a recrystallization structure, achieved through a manufacturing process involving pulverization with a lubricant and annealing, to optimize magnetic properties.

Benefits of technology

The resulting flat metal particles demonstrate enhanced magnetic properties, including reduced hysteresis loss, improved magnetic permeability, and increased magnetic flux density, making them suitable for high-performance iron cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654247000003
    Figure 0007654247000003
  • Figure 0007654247000004
    Figure 0007654247000004
  • Figure 0007654247000005
    Figure 0007654247000005
Patent Text Reader

Abstract

To provide flat metal particles excellent in magnetic properties, etc., such as ferrous metal particles, and a method for manufacturing the same.SOLUTION: Flat metal particles has 0.5 or more of a peak intensity ratio (a peak intensity B / a peak intensity A) of the peak intensity B of a (001) plane to the peak intensity A of a (110) plane in X-ray diffraction, a valley between diffraction peaks from the same crystal plane derived from Kα1 and Kα2 and a volume of 1.8×10-12 m3 or more. A method for manufacturing the flat metal particles comprises: the pulverization step of using coarse grains having a diameter of 200 μm or more as a starting material and pulverizing metal particles by using lubricant and the annealing step of annealing the metal particles pulverized in a flat shape.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to flat metal particles and a method for producing the same, and also to an iron core containing the flat metal particles. [Background technology]

[0002] In metal materials, the texture (also called crystal texture) is controlled to improve their functionality. By controlling the texture, the magnetic properties can be controlled and they are used in iron cores and other applications.

[0003] For example, Patent Document 1 discloses a method for producing flat metal particles having a texture in which the crystal planes are controlled in a predetermined direction by subjecting metal powder containing metal particles to mechanochemical processing such as pulverization. By imparting texture to metal in this way, it is possible to obtain an effect of improving magnetic properties as shown in Patent Document 1, and an effect of improving processability, typically bending, as shown in Patent Document 2.

[0004] Patent Document 1 and Non-Patent Document 1 disclose flat metal particles having a recrystallized texture with crystal planes controlled in a specific direction, and a method for producing the same. In particular, when the flat metal particles are made of an iron-based metal, applying the flat metal particles to the cores of electromagnetic application products such as motors and reactors can improve the magnetic permeability and magnetic flux density of the cores. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2020-70459 A [Patent Document 2] WO2007 / 148712 [Non-patent literature]

[0006] [Non-Patent Document 1] Satoshi Motodzuka et al., Formation of (001) Fiber Texture in Iron Powder and its Effect on Magnetic Properties and Crystal Orientation of the Powder Compact, ISIJ International, Vol.59 (2019), No.1, pp.192-200 Summary of the Invention [Problem to be solved by the invention]

[0007] However, while flattened metal particles of iron-based metals produced by conventional technology have shown improvements in magnetic permeability and magnetic flux density, there is still a need to improve hysteresis loss. That is, it is generally known that such flattened metal particles have better eddy current loss than iron cores produced from electromagnetic steel sheets, but may have worse hysteresis loss. This loss leads to energy loss in motors. The inventors therefore sought to clarify the reason for the increase in hysteresis loss of these iron-based flattened metal particles, and found that the increase in hysteresis loss is due to the surface area per unit mass of the iron-based flattened metal particles, i.e., the specific surface area.

[0008] The present invention provides flat metal particles having excellent magnetic properties, such as suppressing an increase in hysteresis loss, and a method for producing the same. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the following invention meets the above object, thereby completing the present invention.

[0010] <1> In X-ray diffraction, the peak intensity ratio (peak intensity B / peak intensity A) between the peak intensity A of the (110) plane and the peak intensity B of the (001) plane is 0.5 or more, there is a valley between the diffraction peaks from the same crystal plane originating from Kα1 and Kα2, and the volume is 1.8×10 -12 m 3 That's it, flat metal particles. <2> The thickness is 4 μm or more and 250 μm or less, and the specific surface area based on the bottom surface circumscribing the outline in the direction perpendicular to the thickness direction and the surface area calculated as a disk of the thickness is 400 cm 2 / g or less. <1> The flat metal particles described in . <3> The aspect ratio is 3 or more. <1> or <2> The flat metal particles described in . <4> The above <1> ~ <3> A powder iron core comprising a structure in which flat metal particles described in any one of claims 1 to 5 are coated with a binder. <5> A method for producing flat metal particles, comprising the steps of: starting with coarse particles having a diameter of 200 μm or more; a crushing step in which the metal particles are crushed using a lubricant; and an annealing step in which the metal particles crushed into a flat shape are annealed. <6> The method further comprises a first classification step of sieving the metal particles to obtain coarse particles having a diameter of 200 μm or more, prior to the pulverization step. <5> The manufacturing method described in <7> The metal particles crushed into flat particles in the crushing step are dried and sieved to obtain coarse particles having a diameter of 200 μm or more. <5> or <6> A method for producing flat metal particles described in claim 1. <8> The above <5> ~ <7> A method for producing a powder iron core, comprising coating flat metal particles produced by any one of the methods described above with a binder and compressing the particles. Effect of the Invention

[0011] According to the present invention, flat metal particles and the like are provided that have excellent magnetic properties, such as suppressing an increase in hysteresis loss. [Brief description of the drawings]

[0012] [Figure 1] 1 is an image of an iron-based particle according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining losses etc. in a metal particle according to the principle of the present invention. [Diagram 3] FIG. 2 is a schematic diagram for explaining losses etc. in a metal particle according to the principle of the present invention. [Figure 4] A figure to explain an example of calculating the specific surface area of ​​the flat metal particles of the present invention. [Diagram 5] Pole figures of conventional iron particles and flat metal particles of the present invention. [Figure 6] 1 is a graph relating to the aspect ratio and the peak intensity ratio (B / A). [Figure 7] 1 shows powder X-ray diffraction patterns of iron particles before and after a crushing treatment in Example 1. [Figure 8] 1 shows powder X-ray diffraction patterns of iron particles after crushing and annealing in Example 1. [Figure 9] This is a DC BH curve of a ring core obtained by compression molding the flat metal particles after crushing and annealing in Example 1. [Figure 10] 4 is an electron microscope photograph of iron particles before and after a crushing treatment in Comparative Example 1. [Figure 11] 1 shows powder X-ray diffraction patterns of iron particles before and after a crushing treatment in Comparative Example 1. [Figure 12] 1 shows powder X-ray diffraction patterns of iron particles after crushing and annealing in Comparative Example 1. [Figure 13] 1 shows a DC BH curve of a ring core obtained by compression molding flat metal particles after crushing and annealing in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The following is a detailed description of the embodiments of the present invention, but the following description of the constituent elements is one example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following content as long as the gist of the present invention is not changed. Note that in this specification, when the expression "~" is used, it is used as an expression including the numerical values ​​before and after it.

[0014] [Flat metal particles of the present invention] The flat metal particle of the present invention has a peak intensity ratio (peak intensity B / peak intensity A) of 0.5 or more between the peak intensity A of the (110) plane and the peak intensity B of the (001) plane in X-ray diffraction, has a valley between the diffraction peaks from the same crystal plane derived from Kα1 and Kα2, and has a volume of 1.8×10 -12 m 3 The above are flat metal particles.

[0015] [Production method of the present invention] The manufacturing method of the present invention is a method for producing flat metal particles, which includes a crushing step in which coarse particles with a diameter of 200 μm or more are used as a starting material, and the crushed metal particles (iron-based particles) are crushed using a lubricant, and an annealing step in which the crushed metal particles (iron-based particles) into a flat shape are annealed.

[0016] When used in an iron core, the flat metal particles of the present invention have the properties of an iron core made of iron powder, such as excellent eddy current loss characteristics and magnetic flux density, and also have magnetic properties suitable for manufacturing an iron core with excellent hysteresis loss. The manufacturing method of the present invention is a manufacturing method for obtaining such flat metal particles. Note that in this application, the flat metal particles of the present invention can also be manufactured by the manufacturing method of the present invention, and the pressed powder iron core of the present invention uses the flat metal particles of the present invention, and the corresponding configurations in this application can be used mutually.

[0017] As mentioned above, conventional flat metal particles have excellent magnetic permeability and magnetic flux density, but are known to have worse hysteresis loss than laminated cores using electromagnetic steel sheets.

[0018] The inventors conducted research aimed at further improving performance by reducing hysteresis loss in order to maximize the advantages of using such flat metal particles, and found that the specific surface area of ​​the flat metal particles affects the magnitude of hysteresis loss.

[0019] When a magnetic field is applied to soft magnetic particles, the magnetic domain walls move, and the smoother the movement of the magnetic domain walls, the more the hysteresis loss can be reduced. To smooth the movement of the magnetic domain walls, it is essential to use particles with minimal unevenness on the particle surface, which can hinder the movement of the magnetic domain walls within the particles.

[0020] On the other hand, when flattening to improve magnetic permeability and magnetic flux density, the surface area of ​​the particles increases, but the larger the surface area of ​​the particles, the more the number of such irregularities increases and the more susceptible they are to being affected. On the other hand, there is a method of using large particles to reduce the specific surface area while ensuring the necessary surface area, but when large particles are used, there is a risk of increased eddy current loss when an AC magnetic field is applied to a powder iron core formed by pressing multiple such particles together.

[0021] Therefore, in the present invention, further research was conducted on the specific surface area, and flat metal particles with a small specific surface area were discovered by reducing the surface area during flattening and using large, thick flat particles.The present invention also considered the need to ensure a surface area that maintains magnetic permeability and magnetic flux density while keeping the specific surface area small, and therefore found that the volume of the particles is important, since the particle size is necessary (Figures 2 and 3).

[0022] [Flat metal particles] The present invention will now be described in more detail. First, the flat metal particles will be described.

[0023] [Flat plane] The flat iron particles and flat metal particles have a flat surface. The flat surface refers to a surface perpendicular to the thickness direction of the flattened particle. The flat surface is preferably flat. The flat surface may also be a curved surface. Such a flat surface is, for example, a surface formed by plastic deformation caused by subjecting the metal particles to a compression treatment or the like.

[0024] [volume] The volume of the flat metal particles of the present invention is 1.8×10 -12 m 3When the volume of the flat metal particles is equal to or larger than this, the hysteresis loss can be reduced.

[0025] As the metal particles, iron-based particles and the like are used. The iron-based particles used in powdered iron cores generally have an average particle size of about 150 μm. If we consider a particle size of 150 μm as a sphere, the volume of this particle is 1.8 × 10 -12 m 3 This size is considered to be the average volume of a typical iron-based particle.

[0026] In the present invention, the above iron-based particles are flattened to have a volume of the above-mentioned size. This makes it possible to reduce the specific surface area while securing the surface area required for a relatively flat metal particle, thereby reducing the hysteresis loss. The volume is 4.2×10 -12 m 3 More preferably, it is 1.0×10 -11 m 3 It is more preferable that the volume is 4.2×10 or more. The upper limit can be adjusted appropriately based on the size of the powdered iron core, and there is no need to set a specific upper or lower limit. Considering the limitations associated with manufacturing conditions such as processing conditions, the yield rate due to the quality during manufacturing, the availability of materials, the aspect ratio after crushing, etc., the volume is preferably 4.2×10 -9 m 3 It is preferable that:

[0027] Thickness The flat metal particles of the present invention preferably have a thickness of 4 μm or more and 250 μm or less. When the thickness is reduced for flat metal particles of a given size, the particles have a large surface area and a large specific surface area. On the other hand, when the particles are pressed together to form an iron core, the eddy current loss in the cross section in the thickness direction decreases in proportion to the thickness. It is generally known that the relationship between thickness and eddy current loss is expressed by the following formula. Pe (eddy current loss) ∝ (t (thickness of soft magnetic material) f (applied power frequency) Bm (maximum magnetic flux density))^2 ÷ ρ (resistivity of soft magnetic material)

[0028] If the thickness is too large, the effect of improving magnetic permeability and magnetic flux density by flattening is reduced. On the other hand, as the formula shown above shows, an increase in thickness increases eddy current loss. The thickness of electromagnetic steel sheets for laminated cores that compete with powdered iron cores is about 250 μm, and if the iron particles are thicker than this, the advantage of powdered iron cores and iron particles, that is, low eddy current loss, is lost. The lower limit of the thickness may be 5 μm or more. The upper limit of the thickness may be 100 μm or less, or 80 μm or less.

[0029] [Specific surface area] The flat metal particles of the present invention are characterized by a small specific surface area. The flat metal particles of the present invention have a specific surface area of ​​400 cm or less, based on the surface area calculated as a disk of the thickness and the bottom surface circumscribing the outer shape in a direction perpendicular to the thickness direction. 2 It is preferable that the molecular weight is not more than 1 / g.

[0030] Fig. 4 is a diagram for explaining the calculation of the surface area of ​​flat metal particles, etc. The upper part of Fig. 4 relates to iron-based particles before flattening processing. The lower part of Fig. 4 relates to flat metal particles (iron-based particles) after flattening processing.

[0031] As shown in the upper part of Figure 4, the metal particles before flattening have uneven surfaces, but because they are of approximately the same size in all three dimensional directions and have rounded corners, they are regarded as spheres of diameter d and their specific surface area is calculated.

[0032] As shown in the lower part of Figure 4, flat metal particles are flat particles. For flat particles, the specific surface area is calculated by treating them as a disk with particle size d and thickness t. The particle size is calculated based on a plane perpendicular to the thickness direction. The particle size d is calculated by considering it as a circle circumscribing the outline of this plane, and the area of ​​this circle of particle size d is used as the base, and the disk is treated as having a thickness t. The specific surface area of ​​this disk is the specific surface area of ​​the flat metal particle.

[0033] [X-ray diffraction pattern] The flat metal particles of the present invention have a texture in which the axis of easy magnetization is randomly oriented in the in-plane direction of the particle. The texture is formed by crystal rotation when the metal particles are transformed from granular to flattened by crushing and compression, and is characterized as follows.

[0034] That is, in the X-ray diffraction pattern obtained from the flat metal particles, the peak intensity ratio B / A between the peak intensity A of the (110) plane and the peak intensity B of the (001) plane is 0.5 or more. This X-ray diffraction pattern was obtained when a Cu tube was used as the X-ray source. Here, Kα1 and Kα2 refer to characteristic X-rays, whose wavelengths are 1.541 and 1.544 Å when Cu is used as the radiation source. Since the wavelengths are different, two corresponding diffraction peaks appear. This means that there are more (001) planes, which are crystal planes parallel to the surface of the flat metal particles, compared to typical iron particles with random orientation that is not controlled. This (001) plane is the axis of easy magnetization <001> Since iron particles that exhibit such a characteristic X-ray diffraction pattern contain the most, when a magnetic field is applied in a direction parallel to the flat surface, the internal domain walls can move smoothly. The peak intensity ratio B / A is preferably 1 or more.

[0035] It can be easily seen from Fig. 5 that the easy axis of magnetization exists within the plane. Fig. 5(a) is a 001 pole figure of a commercially available iron particle, and Fig. 5(b) is a 001 pole figure of the present flat iron particle obtained by irradiating X-rays from a direction parallel to the flat surface. Compared to the random distribution of pole density of the commercially available iron particle shown in (a), the distribution of pole density of the iron particle according to the present invention shown in (b) is high near the north and south poles and shows a band at the equator. This indicates that the easy axis of magnetization is distributed within the flat surface.

[0036] Increasing the aspect ratio is effective in making more of the easy magnetic axis parallel to the flat surface. On the other hand, if the aspect ratio is made too large, the specific surface area increases, and the advantage of reducing hysteresis loss by controlling the direction of the easy magnetic axis is outweighed by the disadvantage of increased hysteresis loss due to the increased specific surface area. Also, as the aspect ratio increases, eddy current loss decreases. Therefore, when setting the peak intensity ratio B / A, it is necessary to take into account the specific surface area, volume, and aspect ratio of the particle.

[0037] As a basic guideline, the peak intensity ratio B / A is determined by controlling the aspect ratio so that the sum of eddy current loss and hysteresis loss is minimized. In addition, in the applications of the iron core obtained from the iron particles according to the present invention, there are products in which a reduction in eddy current loss is strongly desired and products in which a reduction in hysteresis loss is strongly desired. If the aspect ratio is small, the eddy current loss is large and the hysteresis loss is small. If the aspect ratio is large, the eddy current loss is small and the hysteresis loss is large. Therefore, the appropriate aspect ratio and the optimal value of the peak intensity ratio B / A determined by the aspect ratio also change depending on the application of the product to which this iron core is applied. From this perspective, the peak intensity ratio B / A may be set to a preferable range of less than 8.

[0038] Furthermore, all or a part of the crystal grains constituting the particle have a recrystallized structure.

[0039] The flat metal particles of the present invention include a recrystallized structure in the crystal grains constituting the particles. The recrystallized structure of the flat metal particles of the present invention may be a part of the flat metal particles or may be the entirety of the flat metal particles. From the change in the peak intensity ratio of the flat metal particles, it can be confirmed that the flat metal particles after the pulverization process have an aggregate structure. Since the peaks are sharp, it can be seen that the flat metal particles have a recrystallized structure with reduced strain in the structure. Specifically, from the pattern enlarged in the range of diffraction angles of 60 to 70°, the peaks due to Kα1 and Kα2 of Cu derived from the X-ray source are clearly separated, and a valley is observed between the peaks due to Kα1 and Kα2. This indicates that the magnetization easy axis is arranged parallel to the flat plane, and at the same time, the disorder of the atomic arrangement in the iron particles is reduced. By arranging the magnetization easy axis parallel to the flat plane, when a magnetic field acts parallel to the flat plane, the magnetic domain wall moves smoothly, and the hysteresis loss is reduced. In addition, the reduction in the disorder of the atomic arrangement in the iron particles also smoothes the movement of the magnetic domain wall, and the hysteresis loss is reduced.

[0040] Furthermore, the characteristics of the peaks due to Kα1 and Kα2, including the peak intensity ratio B / A, are set in relation to the volume or specific surface area of ​​the flat particles in order to reduce hysteresis loss. In other words, the mechanism of orientation of the easy axis of magnetization accompanying pulverization and compression using a ball mill or the like is analyzed and examined, and the effect of reducing hysteresis loss due to the volume or specific surface area is taken into account, resulting in flat particles having the volume or specific surface area of ​​the specified size shown above.

[0041] Aspect Ratio The aspect ratio of the flat metal particles of the present invention is preferably 3 or more, more preferably 8 or more. The aspect ratio is calculated as particle diameter d / thickness t, where t is the thickness of the flat metal particles and d is the particle diameter of the flat metal particles. In this case, particle orientation occurs in the molding die, and the direction of the easy axis of magnetization associated with the particle shape can be promoted to be oriented to the compression axis or its perpendicular direction by pulverization and compression molding. As shown in FIG. 6, the above-mentioned peak intensity ratio B / A is proportional to the aspect ratio. Research has shown that this relationship holds regardless of the volume of the particles. In addition, based on the relationship with the volume or specific surface area of ​​the flat metal particles, the increase in hysteresis loss of the molded product using the flat metal particles is suppressed, while improving the magnetic permeability and magnetic flux density, resulting in better magnetic properties. The aspect ratio may be 10 or more.

[0042] The upper limit of the aspect ratio does not need to be particularly set, but if the aspect ratio is too high, the particle diameter d will be too large or the thickness t will be too small, resulting in excessive flattening. For this reason, the upper limit of the aspect ratio may be set to 300 or less. The upper limit of the aspect ratio may also be 200 or less, or 100 or less.

[0043] [Average] The flat metal particles of the present invention are used as a raw material for powdered iron cores, etc. The flat metal particles are an aggregate of many particles. In the present invention, the volume, thickness, specific surface area, aspect ratio, etc. of the particles are average values ​​of the powdered particles of the particles. In determining this average value, particles with a particle size d of 10 μm or less that are difficult to confirm even when observed under a microscope are excluded, and the average value can be taken as the average value of, for example, 30 randomly selected particles.

[0044] [Metal particles] Regarding the flat metal particles of the present invention, the flat metal particles having an aggregate structure have a body-centered cubic lattice structure. The composition of the metal particles is not particularly limited. The metal particles are preferably particles used for dust cores and dust cores. As the metal particles, iron-based particles, which are particles of iron-based materials, are preferably used. For example, the composition of the iron-based material may be pure iron or an iron alloy. Examples of the iron alloy include an iron-cobalt alloy, an iron-cobalt vanadium alloy, an iron-vanadium alloy, a chromium-iron alloy, an iron-aluminum silicon alloy, an iron-silicon chromium alloy, and silicon steel.

[0045] [Molded products] The flat metal particles of the present invention can be used to produce various molded products. As a preferred embodiment of the present invention, the flat metal particles of the present invention can be used to produce a powdered iron core including a structure in which the flat metal particles of the present invention are coated with an insulating film. The molded product using the flat metal particles of the present invention, for example, when produced as a powdered iron core using iron-based particles, has excellent magnetic properties due to its small hysteresis loss and eddy current loss and high magnetic flux density. This powdered iron core is very effective when applied to electromagnetic application products such as iron cores (cores) and reactors for transformers, electric motors, generators, etc., and contributes to improving the functionality of these electromagnetic application products.

[0046] [Powder core] The powdered iron core is not particularly limited as long as it is composed of the above-mentioned flat metal particles and formed to have a predetermined shape. For example, it contains soft magnetic alloy powder and a resin as a binder, and the soft magnetic alloy particles constituting the flat metal particles are fixed to a predetermined shape by being bonded to each other via the resin. The powdered iron core may also be composed of a mixed powder of the above-mentioned flat metal particles and other magnetic powders and formed to a predetermined shape. Furthermore, as shown in FIG. 1, the flat iron particles undergo particle orientation within the iron core, and the orientation has anisotropy.

[0047] [Magnetic parts] The magnetic component is not particularly limited as long as it includes the above-mentioned powdered iron core. For example, the magnetic component may be a powdered iron core having a predetermined shape with an air-core coil around which wire is wound embedded inside the powdered iron core, or a powdered iron core having a predetermined shape with wire wound a predetermined number of times around its surface.

[0048] The flat metal particles of the present invention have a small specific surface area, a strongly developed aggregate structure, and a recrystallized structure. Therefore, the flat metal particles have excellent properties related to the aggregate structure formed. In particular, when the flat metal particles are made of an iron-based metal, the flat metal particles of the present invention and the cores and plates made using the flat metal particles of the present invention have excellent magnetic properties related to the aggregate structure formed. The magnetic components of this embodiment have good voltage resistance, making them suitable for power inductors used in power supply circuits.

[0049] In FIG. 1, the upper part relates to conventional fine powder, and the lower part uses the coarse particles according to the present invention. The appearance before flattening is as shown on the left side of FIG. 1, which is a granular body with no clear features in any three-dimensional direction. By flattening this, the particle size becomes smaller and flatter, as shown in the center row of FIG. 1. The right side of FIG. 1 is an image of a cross section of a powder core molded using the flattened particles. In the cross section of the conventional fine powder in the upper part, it can be seen that there are many places (contact interfaces) where the surfaces of adjacent particles contact each other as a whole, and the contact interfaces are fine, whereas the coarse particles in the lower part have few contact interfaces. From this situation, compared to the cross section of the fine powder, the cross section of the coarse particles in the lower part has fewer contact interfaces that hinder the movement of the magnetic domain walls, so that the effect of molding a powder core by selectively using coarse particles according to the present invention can be clearly confirmed by visual inspection.

[0050] [BH curve] The BH curve referred to here is the relationship between the magnetic field H generated by compressing metal particles into a ring-shaped compact, winding a primary conductor and a secondary conductor around it, and passing a current through the primary conductor, and the magnetic flux B generated by the compact due to that magnetic field.

[0051] The flat metal particles of the present invention, as seen in the BH curve described below, have the property of making the magnetic flux density (B) in the vicinity of the zero point of the magnetic field strength (H) increase sharply with increasing magnetic field, while reducing the area inside the looped BH curve. The flat metal particles of the present invention have a strongly developed aggregate structure and a recrystallized structure, so that the magnetization easy axis is arranged parallel to the flat surface, and the variation in the atomic arrangement is small, so that the magnetic domain wall moves smoothly when a magnetic field acts parallel to the flat surface. Furthermore, since the volume of the particle is large or the specific surface area is small, the magnetic domain wall moves smoothly, so that the magnetic flux density changes immediately in response to changes in the magnetic field, and thus has the property of providing good soft magnetism. In addition, such behavior is particularly due to the smooth movement of the magnetic domain wall, and acts to reduce the area inside the BH curve, which contributes to reducing the so-called hysteresis loss. In addition, as described above, the maximum value of B relative to the maximum value of H applied by the arrangement of the easy magnetization axes can be made to increase, and further the saturation magnetic flux density can be made to increase.

[0052] [Manufacturing method] Next, a method for producing flat metal particles will be described.

[0053] [Production method of the present invention] The method for producing flat metal particles of the present invention uses coarse particles. The method for producing flat metal particles of the present invention can include a first classification step in which a general raw powder of metal particles is classified using a sieve or the like to select only the coarse particles, a crushing step in which the iron particles are crushed using a lubricant, and an annealing step in which the crushed flat iron particles are annealed.

[0054] [First classification process] The first classification step can produce flat metal particles with a large volume and a small specific surface area. The pulverization step can produce flat metal particles with a developed texture. Since the metal particles are pulverized using a lubricant in the pulverization step, the developed texture is maintained even when the metal particles are annealed (heat treated) in the annealing step, and lattice defects (such as processing distortion due to pulverization) can be sufficiently removed. This results in flat metal particles with a low specific surface area, a strongly developed texture, and a recrystallized texture.

[0055] The method for producing flat metal particles includes a classification step for classifying the starting material by particle size, a crushing step for crushing the iron particles using a lubricant, and an annealing step for annealing the flattened crushed iron particles. By making the raw material powder into coarse particles, the classification step can be omitted.

[0056] In the first classification step, coarse particles are obtained by classifying a mixture of metal particles of various particle sizes using a sieve or the like. It is preferable to selectively obtain particles with a diameter of 200 μm or more as the coarse particles. For this purpose, the mixture is sieved using a sieve with a mesh size of 200 μm to remove fine particles and recover the coarse particles.

[0057] [Crushing process] In the milling process, the starting raw material, coarse particles, are milled using a ball mill or other device with a lubricant. This produces flat metal particles with a small volume, low specific surface area, and a well-developed texture. In other words, the number of (111) faces that do not include the axis of easy magnetization in the flat plane is reduced, and the number of (001) faces that include the axis of easy magnetization is increased, resulting in flat metal particles with a texture in which the crystal orientation is controlled in a specific direction.

[0058] [Crushing equipment, etc.] In the pulverization step, the pulverization treatment of the metal particles can be, for example, a mechanochemical treatment in which mechanical energy such as compressive force or frictional force is applied to a particulate material to induce mechanical and chemical interactions between the materials and deform the particle shape. The mechanochemical treatment is not particularly limited, and for example, a mechanical pulverization device can be used. Examples of the device include a bead mill, a planetary, rolling, or vibrating ball mill, a rocking mill, a tower mill, a mechanofusion, a jet mill, a hybridizer, a Henschel mixer, and a homomixer.

[0059] The material of the mill or other grinding container used in the grinding process is not limited, but it is preferable that the container is made of, for example, a metal or metal oxide, because such a material can impart sufficient mechanical energy to the metal particles during the grinding process.

[0060] If a device that does not use spherical media, such as Mechanofusion (manufactured by Hosokawa Micron Corporation), is selected as the device to perform the grinding process, there is no need to add spherical media, and the amount of spherical media introduced can be set to 0.

[0061] When a device using spherical media is selected, the material of the spherical media is not limited, and can be selected according to the size and material of the crushing container. When a spherical medium made of metal or metal oxide is used, sufficient mechanical energy can be imparted to the powder material during the crushing process. The size of the spherical media used in the crushing process is not limited, and can be selected according to the size of the crushing container.

[0062] [Processing time] In the pulverization step, it is preferable to limit the processing time of the pulverization treatment of the metal particles. If the processing time of the pulverization treatment is too long, the specific surface area will become large. The processing time of the pulverization treatment can be appropriately set depending on the pulverization device (e.g., ball mill device) and its conditions (size and mass of balls, rotation speed of container).

[0063] [Lubricant] In the pulverization step, a lubricant is used in the pulverization process of the metal particles. The lubricant may be solid or liquid. The lubricant contains a lubricating substance that exhibits a lubricating function. Here, the lubricant containing a lubricating substance includes not only a lubricant that already contains a lubricating substance, but also a lubricant that forms a lubricating substance on the pressure-receiving surface when it is subjected to pressure due to pulverization, for example.

[0064] The lubricating function means to reduce the coefficient of friction between the metal particles being pulverized and the object (e.g., a spherical medium such as a ball) on which the pulverization process is carried out. By using a lubricant in the pulverization process of metal particles, it is possible to promote the formation of an aggregate structure of the iron particles by the pulverization process.

[0065] As the lubricant, for example, graphite, graphite fluoride, polytetrafluoroethylene, carbon fiber, molybdenum disulfide, mica, talc, boron nitride, etc. can be used. Furthermore, as the liquid lubricant, fatty acid esters and mineral oils can be used. Furthermore, alcohols such as isopropyl alcohol can be used as appropriate as auxiliary agents. For example, the rust-preventive lubricant KURE5-56 (registered trademark), boron nitride, and isopropyl alcohol (IPA) can be used as lubricants when forming the recrystallized structure.

[0066] [Second classification process] The manufacturing method of the present invention may include a second classification step. The second classification step is a step of drying and sieving the metal particles crushed into a flat shape in the crushing step to obtain coarse particles having a diameter of 200 μm or more, and is appropriately performed before the annealing step. That is, the coarse particles are obtained by classifying the fine powder metal particles mixed after the crushing step using a sieve or the like. It is preferable to selectively obtain particles having a diameter of 200 μm or more as the coarse particles. For this purpose, the fine powder and fine particles are removed by sieving using a sieve with an opening of 200 μm, and the coarse particles are recovered. In addition, after the crushing step, the fine powder and fine particles may be in close contact with the coarse particles and difficult to separate, so the particles are dried to make them easier to separate, and then sieved.

[0067] [Annealing process] In the annealing process, the metal particles crushed into flat shapes in the crushing process are annealed (heat treated). By crushing the metal particles using a lubricant in the crushing process, the texture is maintained even when the metal particles are annealed (heat treated) at high temperatures, and the lattice defects (processing distortion) caused by crushing are sufficiently removed, reducing the coercive force. This results in flat metal particles with a developed texture and small local orientation difference. In particular, iron-based metal particles have excellent magnetic properties.

[0068] [Annealing temperature and time] In the annealing process, the crushed flat metal particles may be annealed at a temperature equal to or higher than the recovery / recrystallization temperature of the metal particles. In this case, lattice defects (such as processing distortion due to crushing) can be sufficiently removed and the coercive force can be reduced. This results in flat metal particles with excellent magnetic properties, a highly stable aggregate structure with high crystal orientation and small local orientation difference. The recovery / recrystallization temperature of metal particles varies depending on the composition of the metal particles (pure iron, various iron alloys), processing history, etc.

[0069] For example, in the case of iron particles, the annealing atmosphere can be a hydrogen atmosphere containing argon gas, such as Ar-3%H2. The annealing temperature can be about 600 to 800°C, or about 650 to 750°C. The holding time at the annealing temperature can be about 15 minutes to 2 hours, or about 30 minutes to 1.5 hours. Cooling after holding the annealing temperature can be performed by furnace cooling or the like.

[0070] By this type of production, flat metal particles can be obtained which have a small specific surface area, a large size in the direction perpendicular to the thickness direction, and in which the crystal grains that make up the particles are composed of recrystallized crystals, and in which the crystal planes are parallel to the flat surfaces of the particles.

[0071] Such flat metal particles are manufactured from iron-based particles, mixed with a binder such as an insulating material, coated with the binder, and compressed to obtain a powdered iron core. Such a powdered iron core has excellent magnetic properties such as excellent magnetic permeability and magnetic flux density, and further suppresses an increase in hysteresis loss. EXAMPLES

[0072] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.

[0073] Example 1 (classification) Pure iron particles (manufactured by Kobe Steel, Ltd., product number: ML35N) were sieved to extract coarse particles of 200 μm or more. The volume of these coarse particles was 5.02 × 10 -11 m 3 (0.0502mm 3 ) was.

[0074] (Crushing) The iron particles, boron nitride (manufactured by Nacalai Tesque, Inc., product name: Boron Nitride, product code: 05224-72), and alcohol (manufactured by Wako Pure Chemical Industries, Ltd., product name: 2-propanol, product code: 166-04836) were added to a ball mill (manufactured by Nisshin Giken Co., Ltd., model number: NEV-MA-8) and pulverized.

[0075] The rolling conditions were as follows: 5g of pure iron particles were put into the mill, 0.010g of boron nitride was added as a lubricant, 20mL of alcohol was added, 20 steel balls (SUJ-2) with a diameter of about 10mm were used as spherical media, the ball mill rotation speed was 6.4rps, and the treatment time was 0.75h. A sample with a treatment time of 2.00h was also prepared. After the rolling process, the particles were dried to suppress adhesion between the particles, and sieved through a sieve with a mesh opening of 200μm to obtain rolled coarse iron particles.

[0076] The obtained iron particles were analyzed using an optical microscope (Nikon, LV150N), an electron microscope (JEOL, JCM-6000, etc.), and a powder X-ray diffractometer (Rigaku, Smartlab). The analysis results are shown in Figures 1 and 7, respectively.

[0077] From the raw material particles before sieving as shown in the upper left of Figure 1, the raw material particles after sieving as shown in the lower left of Figure 1 were obtained.

[0078] Processing time 0.75 hours By carrying out the above-mentioned crushing treatment for 0.75 hours, flat iron particles were obtained from the granular iron particles, as shown in the center of Figure 1.

[0079] The shape of the flat metal particle was circumscribed around the outer shape in the direction perpendicular to the thickness direction, and the diameter of the disk was calculated as the same thickness as the thickness of the flat metal particle. The measurement was performed by randomly selecting 30 particles and averaging them. The average diameter of the disks was 1322 μm. The average thickness was 26.71 μm. The volume is 3.67 x 10 -11 m 3 (0.0367mm 3 ) was. -Specific surface area is 100cm 2 / g. (The density of iron was 7.8 g / cm 3 (Calculated as the above disk) The aspect ratio was 49.5 (defined as the ratio of the length at the widest point of the particle to its thickness).

[0080] Processing time 2.00 hours When the treatment time was set to 2.00 h, flat iron particles were obtained. The diameter of the disk was 1692 μm. The average thickness was 6.61 μm. The volume is 1.49 x 10 -11 m 3 (0.0149mm 3 ) was. -Specific surface area is 391cm 2 / g. (The density of iron was 7.8 g / cm 3 (Calculated as the above disk) The aspect ratio was 256 (defined as the ratio of the length at the widest point of the particle to its thickness).

[0081] FIG. 7 shows the powder X-ray diffraction patterns of the raw iron particles and the iron particles subjected to the above-mentioned crushing treatment for 0.75 hours and 2.00 hours. According to this, the peak intensity ratio B / A of the peak intensity A of the (110) plane to the peak intensity B of the (002) plane was as follows: The iron particle size before crushing was 0.25. The iron particles after 0.75 h of grinding treatment were 2.0. The iron particles after 2.00 h of grinding were 18.7.

[0082] From the change in the peak intensity ratio, it was confirmed that an aggregate structure was formed in the iron particles that had been ground for 0.75 and 2.00 hours. In addition, from the pattern enlarged in the diffraction angle range of 60 to 70 degrees, it was found that the diffraction peak of the crystal plane was not separated into two.

[0083] (Annealing) Next, the crushed iron particles were annealed (heat treated) in a tubular electric furnace (TMF-500N, manufactured by AS ONE Corporation). The annealing atmosphere was Ar-3% H2, the annealing temperature was 700°C, the holding time at the annealing temperature was 1h, and the cooling after the temperature holding was furnace-cooled.

[0084] The obtained iron particles were analyzed using a powder X-ray diffractometer (Rigaku Corporation, Smartlab). The analysis results are shown in Figure 8.

[0085] FIG. 8 shows powder X-ray diffraction patterns of the raw iron particles and the iron particles which were subjected to the above-mentioned crushing treatment for 0.75 hours and 2.00 hours and then the above-mentioned annealing treatment. According to this, the peak intensity ratio B / A of the peak intensity A of the (110) plane to the peak intensity B of the (002) plane was as follows: The iron particle size before crushing was 0.25. The iron particles after 0.75 h of grinding treatment were 2.4. The iron particles after 2.00 h of grinding treatment were 20.6.

[0086] From the change in the peak intensity ratio, it was confirmed that an aggregate structure was formed in the iron particles after the crushing process. In addition, the sharpness of the peaks indicates that the particles have a recrystallized structure with reduced strain in the structure.

[0087] Specifically, in the pattern enlarged over the diffraction angle range of 60 to 70°, the peaks due to Cu Kα1 and Kα2 originating from the X-ray source are clearly separated, and a valley is observed between the peaks due to Kα1 and Kα2.

[0088] (Ring core molding) The raw iron particles, the flat metal particles that had been subjected to the above-mentioned crushing treatment for 0.75 hours and then annealed, and the flat iron particles that had been subjected to the above-mentioned crushing treatment for 2.00 hours and then annealed were each compressed in a mold to form a ring core.

[0089] Raw iron particles The external dimensions of each ring core are shown in Table 1. The ring core obtained from the raw iron particles had an outer diameter of 30.15 mm, an inner diameter of 19.8 mm, a thickness of 5.57 mm, a mass of 14.62 g, and a density of 6.47 g / cm. 3 It was.

[0090] Particles milled for 0.75 hours The ring core obtained from the flat metal particles that had been subjected to the above crushing treatment for 0.75 hours and the above annealing treatment had an outer diameter of 30.05 mm, an inner diameter of 19.8 mm, a thickness of 5.36 mm, a mass of 14.20 g, and a density of 6.60 g / cm 3 It was.

[0091] Particles milled for 2.00 hours The ring core obtained from the flat metal particles that had been subjected to the above crushing treatment for 2.00 hours and the above annealing treatment had an outer diameter of 30.08 mm, an inner diameter of 19.8 mm, a thickness of 5.45 mm, a mass of 14.23 g, and a density of 6.49 g / cm 3 It was.

[0092] The ring core was wound with 300 turns of φ0.4 mm coated copper wire as the primary winding and then with 25 turns of φ0.4 mm coated copper wire as the secondary winding, after which a BH curve was obtained using a DC magnetization characteristic tester (Metron Giken Co., Ltd., SK110).

[0093] The excitation conditions were unified at 10,000 A / m. As a result, the BH curves and magnetic properties of each ring core were as shown in Figure 9 and Table 1, and were as follows.

[0094] Raw iron particles The initial relative permeability of the ring core obtained from the raw iron particles was 773, the coercivity was 274 A / m, the hysteresis loss was 10.6 W / kg, and the magnetic flux density was 1.11 T at 10,000 A / m.

[0095] Particles milled for 0.75 hours The ring core obtained from the flat metal particles that had been subjected to the above-mentioned crushing treatment for 0.75 hours and the above-mentioned annealing treatment had an initial relative permeability of 1148, a coercive force of 159 A / m, a hysteresis loss of 7.6 W / kg, and a magnetic flux density of 1.41 T at 10,000 A / m.

[0096] Particles milled for 2.00 hours The ring core obtained from the flat metal particles that had been subjected to the above-mentioned crushing treatment for 2.00 hours and the above-mentioned annealing treatment had an initial relative permeability of 1698, a coercive force of 189 A / m, a hysteresis loss of 10.1 W / kg, and a magnetic flux density of 1.53 T at 10,000 A / m.

[0097] Particles milled for 0.75 hours As described above, compared to the ring cores obtained from raw iron particles, the ring cores obtained from the flat metal particles that were subjected to the above-mentioned crushing process for 0.75 hours and the above-mentioned annealing process had a 49% increase in magnetic permeability, a 29% decrease in hysteresis loss, and a 27% increase in magnetic flux density.

[0098] Particles milled for 2.00 hours The ring core obtained from the flat metal particles that were subjected to the above-mentioned crushing treatment for 2.00 hours and the above-mentioned annealing treatment had a magnetic permeability increased by 120%, a hysteresis loss reduced by 5%, and a magnetic flux density increased by 38%.

[0099] As described above, it has become clear that the application of this technology can significantly improve the magnetic properties of the iron core. In addition, it has been found that shortening the crushing time reduces the hysteresis loss of the iron powder. It has also been found that extending the crushing time increases the magnetic flux density.

[0100] Also, by shortening the pulverization time, limiting the development of the aggregate structure to a certain level, and decreasing the specific surface area, a core with excellent low loss properties can be obtained. On the other hand, by lengthening the pulverization time, promoting the development of the aggregate structure, and increasing the specific surface area, a core with excellent magnetic permeability and magnetic flux density can be obtained. In other words, it is clear that the characteristics of flat iron particles can be controlled by the degree of pulverization.

[0101] [Table 1]

[0102] Table 1 shows the dimensions, mass, and magnetic properties of the ring core obtained by compression molding the flat metal particles after crushing and annealing in Example 1.

[0103] Comparative Example 1 (classification) Pure iron particles (manufactured by Kobe Steel, Ltd., product number: ML35N) were used without sieving. The particle size distribution of these iron particles was as follows. The volume of these particles was calculated as 1.77 x 10 spheres with a diameter of 150 μm, which is equivalent to the median diameter D50. -12 m 3 (0.00177mm 3 ) was decided. 250μm or more: 23.6% by weight, 180~250μm: 16.9% by weight, 106 to 150 μm is 11.0% by weight, 75 to 106 μm is 15.4% by weight, 63 to 75 μm: 5.3% by weight; 45 to 63 μm: 5.9% by weight; 3.7% by weight of 45 μm or less

[0104] (Crushing) The iron particles, boron nitride (manufactured by Nacalai Tesque, Inc., product name: Boron Nitride, product code: 05224-72), and alcohol (manufactured by Wako Pure Chemical Industries, Ltd., product name: 2-propanol, product code: 166-04836) were added to a ball mill (manufactured by Nisshin Giken Co., Ltd., model number: NEV-MA-8) and pulverized.

[0105] The processing conditions were as follows: 5g of pure iron particles were put into the mill, 0.010g of boron nitride was added as a lubricant, 20mL of alcohol was added, 20 steel balls (SUJ-2) with a diameter of about 10mm were used as spherical media, the ball mill rotation speed was 6.4rps, and the processing time was 0.75h. For comparison, a sample with a processing time of 2.00h was also prepared.

[0106] The obtained iron particles were analyzed using an optical microscope (Nikon, LV150N), an electron microscope (JEOL, JCM-6000, etc.), and a powder X-ray diffractometer (Rigaku, Smartlab). The analysis results are shown in Figures 10 and 11, respectively.

[0107] Particles milled for 0.75 hours As shown in Figure 10(a), the above-mentioned crushing process was carried out for 0.75 hours to obtain flat iron particles. The shape of this flat metal particle was circumscribed to the outer shape in the direction perpendicular to the thickness direction, and the diameter of the disk (particle size) was calculated by assuming the thickness to be the same as that of the flat metal particle. The average diameter of the disks was 216 μm. The average thickness was 10.20 μm. The volume is 3.74 x 10 -13 m 3 (0.000374mm 3 ) was. -Specific surface area is 275cm 2 / g. (The density of iron was 7.8 g / cm 3 (Calculated as the above disk) The aspect ratio was 27.0 (defined as the ratio of the length at the widest point of the particle to its thickness).

[0108] Particles milled for 2.00 hours When the treatment time was set to 2.00 h, the particles shown in FIG. 10(b) were obtained, and had the following sizes: The diameter of the disk was 498 μm. The average thickness was 3.34 μm. The volume is 6.51 x 10 -13 m 3 (0.000651mm 3 ) was. -Specific surface area is 778cm 2 / g. (The density of iron was 7.8 g / cm 3 (Calculated as for this disc) The aspect ratio was 149 (defined as the ratio of the length at the widest point of the particle to its thickness).

[0109] FIG. 11 shows the powder X-ray diffraction patterns of the raw iron particles and the iron particles subjected to the above-mentioned crushing treatment for 0.75 hours and 2.00 hours. According to this, the peak intensity ratio B / A of the peak intensity A of the (110) plane to the peak intensity B of the (002) plane was 0.25 for the iron particles before the crushing treatment. The iron particles after 0.75 h of grinding treatment were 4.01. The iron particles after 2.00 h of grinding treatment were 11.8. From the change in the peak intensity ratio, it was confirmed that an aggregate structure was formed in the iron particles after the crushing process. In addition, from the pattern enlarged in the diffraction angle range of 60 to 70 degrees, it was found that the diffraction peak of the crystal plane was not separated into two.

[0110] (Annealing) Next, the crushed iron particles were annealed (heat treated) in a tubular electric furnace (TMF-500N, manufactured by AS ONE Corporation). The annealing atmosphere was Ar-3% H2, the annealing temperature was 700°C, the holding time at the annealing temperature was 1h, and the cooling after the temperature holding was furnace-cooled.

[0111] The obtained iron particles were analyzed using a powder X-ray diffractometer (Rigaku Corporation, Smartlab). The analysis results are shown in FIG.

[0112] FIG. 12 shows the powder X-ray diffraction patterns of the raw iron particles and the iron particles subjected to the above-mentioned crushing treatment for 0.75 hours and 2.00 hours. According to this, the peak intensity ratio B / A of the peak intensity A of the (110) plane to the peak intensity B of the (002) plane was 0.25 for the iron particles before the crushing treatment. The iron particles after 0.75 h of grinding treatment were 2.08. The iron particles after 2.00 h of grinding treatment were 7.04. From the change in the peak intensity ratio, it was confirmed that an aggregate structure was formed in the iron particles after the crushing process. In addition, the sharper peaks indicate that the particles have a recrystallized structure with reduced strain in the structure. Specifically, from the pattern enlarged in the diffraction angle range of 60 to 70°, the peaks due to Cu Kα1 and Kα2 derived from the X-ray source are clearly separated, and a valley is observed between the peaks due to Kα1 and Kα2.

[0113] (Ring core molding) The raw iron particles, the flat metal particles that had been subjected to the above-mentioned crushing treatment for 0.75 hours and then annealed, and the flat iron particles that had been subjected to the above-mentioned crushing treatment for 2.00 hours and then annealed were compressed in a die to form a ring core. The external shape of each ring core was as shown in Table 2.

[0114] Raw iron particles The ring core obtained from the raw iron particles had an outer diameter of 30.05 mm, an inner diameter of 19.92 mm, a thickness of 2.57 mm, a mass of 6.14 g, and a density of 6.00 g / cm. 3 It was.

[0115] Particles milled for 0.75 hours The ring core obtained from the flat metal particles that had been subjected to the above crushing treatment for 0.75 hours and the above annealing treatment had an outer diameter of 30.04 mm, an inner diameter of 19.93 mm, a thickness of 2.36 mm, a mass of 5.93 g, and a density of 6.34 g / cm 3 It was.

[0116] Particles milled for 2.00 hours The ring core obtained from the flat metal particles that had been subjected to the above crushing treatment for 2.00 hours and the above annealing treatment had an outer diameter of 30.07 mm, an inner diameter of 19.93 mm, a thickness of 2.39 mm, a mass of 5.97 g, and a density of 6.28 g / cm 3 It was.

[0117] The ring core was wound with 300 turns of φ0.4mm coated copper wire as the primary winding, and 25 turns of φ0.4mm coated copper wire as the secondary winding, and then a BH curve was obtained using a DC magnetization characteristic tester (Metron Giken Co., Ltd., SK110). The excitation conditions were unified at 10,000A / m. As a result, the BH curves and magnetic properties of each ring core are shown in FIG. 13 and Table 2, and the physical properties were as follows.

[0118] Raw iron particles The initial relative permeability of the ring core obtained from the raw material iron particles was 726, the coercive force was 157 A / m, the hysteresis loss was 5.96 W / kg, and the magnetic flux density was 1.00 T at 10,000 A / m.

[0119] Particles milled for 0.75 hours The ring core obtained from the flat metal particles that had been subjected to the above-mentioned crushing treatment for 0.75 hours and the above-mentioned annealing treatment had an initial relative permeability of 830, a coercive force of 272 A / m, a hysteresis loss of 13.5 W / kg, and a magnetic flux density of 1.34 T at 10,000 A / m.

[0120] Particles milled for 2.00 hours The ring core obtained from the flat metal particles that had been subjected to the above-mentioned crushing treatment for 2.00 hours and the above-mentioned annealing treatment had an initial relative permeability of 1023, a coercive force of 277 A / m, a hysteresis loss of 13.5 W / kg, and a magnetic flux density of 1.39 T at 10,000 A / m.

[0121] As described above, compared to the ring cores obtained from raw iron particles, the ring cores obtained from the flat metal particles that were subjected to the above-mentioned crushing process for 0.75 hours and the above-mentioned annealing process had a 14% increase in magnetic permeability, a 108% increase in hysteresis loss, and a 34% increase in magnetic flux density. The ring core obtained from the flat metal particles that were subjected to the above crushing process for 2.00 hours and the above annealing process showed a 41% increase in magnetic permeability, a 127% increase in hysteresis loss, and a 39% increase in magnetic flux density.

[0122] As described above, even if the raw powder is crushed and heat-treated without sieving, that is, without any effort to reduce the specific surface area, improvements in magnetic permeability and magnetic flux density are observed, but hysteresis loss worsens. Therefore, it has become clear that the magnetic properties of the iron core can be significantly improved by applying this technology, which involves efforts to reduce the specific surface area.

[0123] [Table 2]

[0124] Table 2 shows the dimensions, mass, and magnetic properties of the ring core obtained by compression molding the flat metal particles after crushing and annealing in Comparative Example 1. [Industrial Applicability]

[0125] The flat metal particles of the present invention can be used for powdered iron cores used in motors, etc., and are therefore industrially useful.

Claims

1. In X-ray diffraction, the peak intensity ratio (peak intensity B / peak intensity A) of the peak intensity A of the (110) plane to the peak intensity B of the (001) plane is 0.5 or more and less than 8, and a valley is present between the diffraction peaks from the same crystal plane originating from Kα1 and Kα2, The volume is 1.8 x 10 -12 m 3 The flat metal particles have an area of ​​4.2×10 −9 m 3 or less.

2. The thickness is 4 μm or more and 250 μm or less, The specific surface area is 400 cm based on the surface area calculated as a disk of the thickness and the bottom surface circumscribing the outline in the direction perpendicular to the thickness direction. 2 The flat metal particles described in claim 1, having a molecular weight of 1 / g or less.

3. The flat metal particles according to claim 1 or 2, having an aspect ratio of 3 or more.

4. A powder iron core comprising a structure in which flat metal particles according to any one of claims 1 to 3 are coated with a binder.

5. A crushing step of crushing coarse metal particles having a diameter of 200 μm or more as a starting material using a lubricant; A method for producing flat metal particles, comprising an annealing step of annealing the metal particles crushed into a flat shape.

6. 6. The method according to claim 5, further comprising a first classification step, prior to the pulverization step, of sieving the metal particles to obtain coarse metal particles having a diameter of 200 μm or more as the starting material for the pulverization step.

7. A method for producing flat metal particles as described in claim 5 or 6, comprising a second classification step in which the metal particles crushed into a flat shape in the crushing step are dried and sieved to obtain coarse particles having a diameter of 200 μm or more.

8. A method for producing a powdered iron core, comprising coating flat metal particles produced by the method according to any one of claims 5 to 7 with a binder and compressing the coated flat metal particles.

Citation Information

Patent Citations

  • Oriented dust core

    JP2010010501A

  • Flat iron particle and production method thereof

    JP2020070459A

  • Copper-based rolled alloy and method for producing the same

    WO2007148712A1

  • X-ray spectroscopic analysis device and chemical state analysis device using said x-ray spectroscopic analysis device

    WO2019064360A1